A Study on Improvement of the Military IdAM Using Edge-Sovereign Identity (ESI) - Park, Gyudong; Jeon, Gi-Yoon; Kim, Jong-Oh (Journal of Web Engineering, 2022)
A framework-level IdAM integration approach requires a stable network infrastructure. Information framework’s operation may be significantly restricted when the network is disconnected from the remote IdAM service. Moreover, military networks, especially tactical networks, are volatile, and network disconnection is also high. In this paper, we proposed an Edge-Sovereign Identity (ESI) that expanded the concept of SSI for use in the military field, designed the structure and function of the proposed concept, and demonstrated its usefulness and validity through examples and prototypes.